Setting up and running a small flour mill or bakery - Axtell, Barrie; Fellows, Peter (Technical Centre for Agricultural and Rural Cooperation, 2004)
This series of practical guides is aimed at people starting or operating a food business. The third publication in the series covers markets for flours and bakery products, setting up a mill or a bakery, processing grains and flours and producing bakery products, quality assurance and legislation, and production and financial management. (See also 1041, 1175)